ANALYSIS OF FACTORS AFFECTING THE USE OF QRIS (QUICK RESPONSE CODE INDONESIAN STANDART) AS A PAYMENT TOOL AMONG MSME MERCHANTS IN PEKANBARU CITY - Puri,S.E, Virginia Asoka; Widayatsari, SE,M.SE, Dr. Any; Maulida S.E., M.Si, Dr. Yusni (Inovbiz: Jurnal Inovasi Bisnis, 2023)
This research aims to identify factors that influence the use of Quick Response Code Indonesia Standard (QRIS) as a payment tool on MSMEs merchants in Pekanbaru City. QRIS has been officialized by Bank Indonesia as a digital payment transaction tool that makes it easier for consumers and merchants to make transactions. In this study, transaction costs and revenue are used as independent variabels, while the use of QRIS as a means of payment becomes dependent variabels. The method used in this research is a quantitative method using a likert scale questionnaire and data converted to an interval scale, respondents in this study amounted to a hundred MSMEs Â merchants. Data was then analyzed using double linear regression with the help of SPSS version 24. The results show that simultaneously or partially, transaction cost and revenue factors have a significant influence on the use of QRIS as a digital payment transaction tool in MSMEs merchants in Pekanbaru City. The implication of this study is that the cost of MDR transactions and settlements spent on using QRIS is comparable to the benefits obtained, including increased business revenue. This research could provide a clearer insight for MSMEs in considering the use of QRIS as an effective and efficient means of payment.